Prediksi Harga Bawang Merah menggunakan Algoritma Fuzzy Inference System (FIS) - Agus Salim; Nur Rofiq (STMIK Budi Darma, 2023)
Consumption of shallots in Indonesia is still relatively large. This affects price movements, production to market needs. Associated with changes in the amount of production with public consumption needs affect the price variations in each period. Shallot price conditions in the market that experience changes can affect losses or profits for shallot entrepreneurs. This creates problems in the sale of bawal because the price of onions is difficult to predict. To minimize losses, a system or technology is needed that can help predict shallot prices. As an illustration of the shallot entrepreneurs. Shallot price prediction system can be done using the calculation method